Performance test and controller design of passive thermosiphon beam - Ramesh, Arpitha Rani (2018)
Thermosiphon beams fall under the integrated system of Air Conditioning and Mechanical Ventilation (ACMV). An ACMV thermosiphon beam system is designed to meet the environmental comfort needs in a closed space environment. The traditional ACMV systems such as chilled beam systems being used have a huge impact on the energy requirement of the buildings. Though chilled beams are favored by customers because of their immense scope, there are several constraints that have limited their applications in hot and/or hot and humid regions. In order to overcome the drawbacks of chilled beam systems, Active Thermosiphon Beam (ATB) and Passive Thermosiphon Beam (PTB) air distribution schemes were developed. ATB and PTB are favored as one of the best solutions in terms of comfort, energy, and cost. This thesis describes the basic phenomena, experimental setup and detailed working procedure of PTB. It includes the tests that were conducted to demonstrate the performance of the system by showing the effects of primary air supply, the location of air ion generator and the length of fall duct on negative ion concentration in the room. The results are validated with appropriate graphical representation. In addition, this thesis also discusses implementing a suitable control for controlling the room temperature and carbon dioxide concentration. Simulink - Matlab is used for the design of controller, tuning, and implementation. The response of PID and Fuzzy PID controllers are demonstrated and analyzed in detail in this report.